Consumer Behaviour in Online Travel: How Does Continuous Purchase Behaviour Formed in Digital Age? - Pratminingsih, Sri Astuti; Zulganef, Zulganef; Purwaningdyah, Sri Wiludjeng Sunu; Syafie, Nur Aima (Jurnal Manajemen Bisnis, 2024)
Research aims: This study aims to understand the role of perceived ease of use, information service function, consumer expectation, and user satisfaction in determining continuous purchase behavior in online travel application users, while considers consumer experience as a moderating variable.Design/Methodology/Approach: This study is carried out using quantitative approach. The data is collected by distributing online questionnaire to users of e-travel application in West Java, Indonesia chosen using purposive sampling. The data is processed using Structural Equation Modeling with Partial Least Square (SEM PLS).Research findings: The results indicate that perceived ease of use, information service function, consumer expectation, and user satisfaction can explain customers’ continuous purchase behavior. In addition, consumer experience can moderate the relationship between user satisfaction and continuous purchase behavior, by which higher experience strengthens the relationship. Theoretical Contribution/Originality: This study contributes to enrich the understanding of how user satisfaction affects continuous purchase behavior by looking at the variables of perceived ease of use, information service function, and user expectation.Practitioners/Policy Implications: This study can be of interest to service providers, especially e-travel application, to provide a good, easy to understand services, as well as information and comfort for its users to remain loyal in using the application.Research Limitations/Implications: This study is only limited to one object, namely users of e-travel application. Future research can use different objects and consider additional variables such as review credibility and perceived enjoyment in determining continuous purchase behavior.